Histological Structure of the Integument in Mastacembelus mastacembelus (Solander) (Baghdad Science Journal, 2025)
The histological structure of integument in Mastacembelus mastacembelus have been investigated from skin fragments cut from nine regions at body surface.The results revealed that the integument of the fish investigated comprises three principal layers- the epidermis, the dermis (corium) and the subcutis-All the three principal layers may further be divided into secondary layers according to the function performed by their cells. The epidermis may further divided into three layers- the outermost epithelial coverage, the middle layer and the basal layer (stratum germinatiuum)-The dermis consists of a relatively thin upper layer of loose vascular connective tissue called the stratum laxum and a thick lower compact layer- the stratum compactum. The upper loose layer contains blood capillaries, nerve fibers and scale pockets. The subcutis is the innermost and the thinnest layer of the skin and is situated in between the stratum compactum and the muscles. All the above main layers showed great extend in their thickness.